2016
DOI: 10.1007/s00595-016-1339-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfibrinogenemia is associated with inflammatory mediators and poor prognosis in patients with gastric cancer

Abstract: Preoperative hyperfibrinogenemia was associated with tumor progression, inflammatory mediators, and poor overall survival in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 17 publications
3
37
1
Order By: Relevance
“…The independent prognostic value of increased fibrinogen level has been demonstrated in 351 surgically treated gastric cancer patients. The hazard ratio was 2.61 (95% CI = 1.18-5.76) as reported by Suzuki et al [111]. The independent prognostic role was confirmed in another large surgically treated cohort of 1196 gastric cancer patients [112].…”
Section: Fibrinogen In Gastric Cancer Evaluationsupporting
confidence: 62%
“…The independent prognostic value of increased fibrinogen level has been demonstrated in 351 surgically treated gastric cancer patients. The hazard ratio was 2.61 (95% CI = 1.18-5.76) as reported by Suzuki et al [111]. The independent prognostic role was confirmed in another large surgically treated cohort of 1196 gastric cancer patients [112].…”
Section: Fibrinogen In Gastric Cancer Evaluationsupporting
confidence: 62%
“…In a cohort of 315 GC patients undergoing surgery, Suzuki et al 111 showed that tumor progression was significantly associated with hyperfibrinogenemia concomitant with inflammation evaluated with protein C-reactive levels, and plasma FBG levels significantly decreased after radical surgery. In this study, hyperfibrinogenemia emerged as an independent prognostic factor for poor survival.…”
mentioning
confidence: 99%
“…The clinical prognosis of advanced gastric cancer is poor; therefore, multimodal treatments before and/or after operation are being developed . The identification of new suitable biomarkers for predicting prognosis is increasingly important to determine whether patients should or should not receive neoadjuvant or adjuvant therapy …”
mentioning
confidence: 99%
“…(2)(3)(4) The identification of new suitable biomarkers for predicting prognosis is increasingly important to determine whether patients should or should not receive neoadjuvant or adjuvant therapy. (5,6) In 1977, leucine-rich a2-glycoprotein-1 (LRG1) was the first identified member of the leucine-rich repeat family in human serum. (7) It is an approximately 50-kDa secreted glycoprotein that contains eight repeating consensus sequences with a leucine-rich motif.…”
mentioning
confidence: 99%